2022
DOI: 10.47067/ramss.v5i2.217
|View full text |Cite
|
Sign up to set email alerts
|

Military Expenditures, Income Inequality and Economic Growth Interlinkages: An Empirical Assessment for Developing Countries

Abstract: The precise objective of the research is to empirically analyze the interdependence between military expenditure, income inequality and economic growth in 51 developing nations. For this purpose, study is used aggregate and disaggregate data analysis of developing countries on the basis of democracy. To tackle the endogeneity between the variables, three-stage least squares (3SLS) econometric technique is used for the current analysis by using dataset spanning over 2000-2020.  Data for the variables used is ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…The health of an economy is determined by stock trading performance. It increases the trading of goods and services within the economy, boosts the total amount of investment in the various businesses operating in national boundaries, and concentrates on the management and operational effectiveness of these businesses (Alfaro, Chari, Greenland, & Schott, 2020;Gillani, Ahmed, Khan, & Hussain, 2022). Several financial and economic factors like financial credits, financial deposits, economic growth, industrialization, and employment rate affect stock trading performance.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The health of an economy is determined by stock trading performance. It increases the trading of goods and services within the economy, boosts the total amount of investment in the various businesses operating in national boundaries, and concentrates on the management and operational effectiveness of these businesses (Alfaro, Chari, Greenland, & Schott, 2020;Gillani, Ahmed, Khan, & Hussain, 2022). Several financial and economic factors like financial credits, financial deposits, economic growth, industrialization, and employment rate affect stock trading performance.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Tchamyou, Asongu, and Odhiambo (2019) investigates the role of ICT and education on income inequality in African Countries, and claimed the education as lifelong learning leads to enhance to income level of the poor and the rich-poor gap reduces over time. Şenol and Orhan (2021) raise importance of conducting research on income inequality in the emerging economies and found that the improvement in education level and health leads to reduce income inequality in the OECD countries (Gillani, Ahmed, Khan, & Hussain, 2022). Ahmad, Shafiq, and Gillani (2019) shows that remittances have an impact on health and education but it improves health in high income countries more as compare to low-income countries while school enrollment increased in low-income countries more (Shafiq & Gillani, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…This is dependent on the institutions and military spending levels attained by these emerging nations. Gillani et al (2022) used the 51 developing countries data from 2000-2020 and employ 3SLS techniques for estimation. They found that the DE shows that higher level of DE reduces the INE and economic growth.…”
mentioning
confidence: 99%